(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article clarifies the terminology, related to online counseling, analyzes the opportunities of the counseling and online psychotherapy, particularly in working with a couple and family, 257 Actual Problems of Psychology in Educational Institutions. 2021. Issue 11 considers their advantages, including anonymity, confidentiality, security; accessibility, mobility, expanding the vision of the therapeutic context; an opportunity of using the most methods, the same as in offline counseling. The article clarifies researches, which proves the effectiveness of consulting online, defines the main problems, which clients discuss during online counseling, provides practical recommendations regarding the organization of the online counseling process and the consideration of the limitations. of working in this way, defines the strategies of the behavior in case of technical problems during providing psychological assistance